EVALUATION OF THE EFFICIENCY OF THE FINANCIAL PERFORMANCE OF THE FIRST ISLAMIC INSURANCE COMPANY IN JORDAN WITH A PROPOSED MODEL FOR THE ESTABLISHMENT OF AN ISLAMIC INSURANCE COMPANY IN IRAQ (World Economics and Finance Bulletin, 2023)
The current research aims to present the theoretical framework for Islamic (Takaful) insurance, and what is the role of financial performance evaluation using financial ratios in the development of the profitability of insurance companies, and to present the reality of Islamic insurance in Iraq. The research adopted the descriptive analytical approach, and the financial statements of the First Islamic Insurance Company in the Jordanian insurance sector were used for the period (2011-2020), and an applied model was proposed to establish an Islamic insurance company in Iraq. The research reached a number of conclusions, most notably: The insurance market in Iraq There is a need to establish an Islamic (symbiotic) insurance company, in order to develop and diversify insurance services. The research recommended a number of recommendations, the most important of which are: And training cadres to work on the requirements and conditions of Islamic insurance
Keywords: financial analysis; Jordanian Islamic insurance sector; a proposed model for an Islamic insurance